Word-of-mouth in contemporary Hollywood - Hewitt, Simon (Routledge, 2023)
Word-of-Mouth in Contemporary Hollywood provides a unique insight into the potential for online communication to enable audiences to exert a greater impact on film industrial practices than ever before.
Introduction: What is Word-of-Mouth? 1. Word-of-Mouth and Bourdieu-economics 2. The Package-Unit-Fan System of Hollywood Film Financing 3. Grassroots Intermediaries and Contemporary Hollywood Film Marketing 4. Crowdsourced Cinema and the 'New' World of Hollywood Film Distribution 5. Please Turn Your Phones On: The Future of Hollywood Film Exhibition Conclusion: The Gift Economy, Commodity Culture, and Word-of-Mouth . - Includes bibliographical references and index. - Description based on CIP data; resource not viewed
Keywords: Motion picture industry -- California -- Los Angeles; Motion picture audiences -- United States; Word-of-mouth advertising -- United States; Cinéma; Industrie; Californie; Los Angeles; Cinéma; Publics; États-Unis; Bouche-à-oreille (Publicité); États-Unis; Motion picture audiences; Motion picture industry; Word-of-mouth advertising; California; Los Angeles; United States